2023
DOI: 10.1111/apha.13986
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological mechanisms of reduced physical activity: Insights from the human step reduction model and animal analogues

Abstract: Physical inactivity represents a heavy burden for modern societies and is spreading worldwide, it is a recognised pandemic and is the fourth cause of global mortality. Not surprisingly, there is an increasing interest in longitudinal studies on the impact of reduced physical activity on different physiological systems. This narrative review focuses on the pathophysiological mechanisms of step reduction (SR), an experimental paradigm that involves a sudden decrease in participants' habitual daily steps to a low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 134 publications
0
4
0
Order By: Relevance
“…[ 20 ] A study on animals also confirmed that sedentary rats had decreased fatty acid oxidation ability and increased fat mass, and the fat mass increase rate of older rats was higher. [ 23 ] This makes a mechanism contribution to the increase of CVD risk. In addition, sedentary time has been shown to be associated with inflammatory markers (C-reactive protein).…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] A study on animals also confirmed that sedentary rats had decreased fatty acid oxidation ability and increased fat mass, and the fat mass increase rate of older rats was higher. [ 23 ] This makes a mechanism contribution to the increase of CVD risk. In addition, sedentary time has been shown to be associated with inflammatory markers (C-reactive protein).…”
Section: Discussionmentioning
confidence: 99%
“…They also summarize validations that exercise can counteract the negative effects. 21 Exercise puts muscle tissue into stress. Particularly, the endoplasmic reticulum (ER) undergoes stress-related adaptations.…”
Section: Physical Activity Over Physical Restmentioning
confidence: 99%
“…In particular, decrements in muscle mass, muscle function, muscle protein synthesis, cardiorespiratory fitness, endothelial function, and insulin sensitivity, together with an increased fat mass and inflammation, have been observed. They also summarize validations that exercise can counteract the negative effects 21 …”
Section: Muscle Tissue Prefers Physical Activity Over Physical Restmentioning
confidence: 99%
“…recently developed a deep learning–based platform for an in‐depth, automated fiber and nucleus type analysis, to significantly improve the characterization of affected muscle fibers in, for example, degenerative disease [reviewed in 9]. In turn, organelle plasticity also mediates the downside of exercise adaptation, that is, the negative, pathophysiological mechanisms of a reduction in physical activity 10 …”
mentioning
confidence: 99%